Tripping in the happiest country of the world: use values of psychedelics according to Finnish users - Tsupari, Mika (Contemporary drug problems, 2025)
Background: The use of psychedelics is on the rise worldwide as more people are experimenting, self-medicating or seeking benefits from these substances. Aims: This study explores the use values ascribed to classic psychedelics by 40 users in Finland – a country that scores high in welfare and happiness but has faced an increase in mental health problems and has adapted austerity policies in the public service sector.Methods: The data consists of thematical interviews with individuals who use or have used psychedelics. We analysed the data focusing on the sense-making regarding use practices and use values. Results: The analysis identified three main functions and benefits: (a) psychedelics as a catalyst for change, (b) psychedelics as a self-medication practice and (c) psychedelics as a device for self-improvement. Positive experiences included feelings of beauty, calmness, awe, connecting with others and mystical experiences. Psychedelics had helped the participants with depression, anxiety, difficult experiences and traumas. Conclusions: Psychedelics appear to offer users experiences that are unattainable in their everyday lives. Their use can be seen as part of a contemporary biopolitical project of self-care and individualistic solutions for contemporary need for better mental health, living a carefree and meaningful life. When certain harm and risk reduction practices are considered, psychedelic use still seems likely to provide more benefits than harm for some individuals.